2018
DOI: 10.1002/ijc.31615
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic inhibition of MICA sheddase ADAM17 by lomofungin in hepatocellular carcinoma cells

Abstract: In our previous study on hepatocellular carcinoma (HCC) susceptibility genes in chronic hepatitis patients, we identified the MHC class I polypeptide-related sequence A (MICA). Natural killer cells eliminate various cancer cells, including HCC, by suppressing MICA shedding. Therefore, we investigated MICA sheddases and inhibitors for HCC immunotherapy. In this study, HepG2, PLC/PRF/5, and Hep3B were treated with the siRNA of a disintegrin and metalloproteases (ADAMs) and matrix metalloproteases to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…At each time-point, ISG mRNA level was adjusted to the level of the internal control and quantified, as previously described. 16 There was no significant difference in the male/female ratio, age, log HCV RNA in the serum (log/mL), platelet count, and levels of alanine aminotransferase (ALT) and γ-GTP between the patients with HCV genotypes 1 and 2 ( Table 1). The positive rates of HCV RNA in B cells were significantly higher in CH-C patients with G1 than in those with G2 (P < 0.001) [G1, 110/132 (83.3%); G2, 20/40 (50.0%)].…”
Section: Evaluation Of Levels Of the Isg Mrnamentioning
confidence: 91%
“…At each time-point, ISG mRNA level was adjusted to the level of the internal control and quantified, as previously described. 16 There was no significant difference in the male/female ratio, age, log HCV RNA in the serum (log/mL), platelet count, and levels of alanine aminotransferase (ALT) and γ-GTP between the patients with HCV genotypes 1 and 2 ( Table 1). The positive rates of HCV RNA in B cells were significantly higher in CH-C patients with G1 than in those with G2 (P < 0.001) [G1, 110/132 (83.3%); G2, 20/40 (50.0%)].…”
Section: Evaluation Of Levels Of the Isg Mrnamentioning
confidence: 91%
“…According to Jinushi et al, the amount of soluble MICA was high in several patients with HCC, and their respective peripheral NK cells had reduced amounts of NKG2D expression and showed impaired activation [ 82 ]. This detrimental function of soluble MICA, enables cancer cells to evade the NK cell-mediated immune surveillance [ 83 ]. Among the MICA-shedding proteases, the roles of a disintegrin and metalloproteases 17 (ADAM17), were emphasized recently [ 83 ].…”
Section: Nk Cell Dysfunction In Hccmentioning
confidence: 99%
“…This detrimental function of soluble MICA, enables cancer cells to evade the NK cell-mediated immune surveillance [ 83 ]. Among the MICA-shedding proteases, the roles of a disintegrin and metalloproteases 17 (ADAM17), were emphasized recently [ 83 ]. ADAM17 knockdown reduced the soluble MICA levels and increased the membrane-bound MICA expression in HCC cell lines, thereby allowing for the cells to be killed by NK cells ( Figure 1 ) [ 83 ].…”
Section: Nk Cell Dysfunction In Hccmentioning
confidence: 99%
“…In the HCC setting, it has been shown that ADAM9, which is overexpressed in HCC tissue, was involved in MICA shedding at the level of an intracellular cleavage resulting in the release of the soluble form of MICA [49]. Interestingly, decreased sMICA levels and increased membrane-bound MICA expression in HCC could be attained by ADAM17 knockdown [50], an enzymatic pathway which is also involved in the control of FcγRIII shedding in chronic HCV infection [51]. Regorafenib, a small molecule inhibitor of multiple kinases approved for treatment of sorafenib-resistant HCC, inhibited mRNA and protein expression of ADAM9 and ADAM10 in HCC cell lines, resulting in higher membrane MICA expression and conversely lower sMICA levels [52], similarly to the popular aldehyde dehydrogenase inhibitor disulfiram which suppresses ADAM10 activity [53].…”
Section: Alteration Of the Nkg2d-mica/b Axis In Hccmentioning
confidence: 99%